Shear Wave Elastography Based on Noise Correlation and Time Reversal - Brum, Javier; Benech, Nicolás; Gallot, Thomas; Negreira, Carlos (Frontiers in Physics, 2021)
Shear wave elastography (SWE) relies on the generation and tracking of coherent shear waves. Recent technological developments have allowed SWE to be implemented in commercial ultrasound and magnetic resonance imaging systems, quickly becoming a new imaging modality in medicine and biology. However, coherent shear wave tracking sets a limitation to SWE because it either requires ultrafast frame rates (of up to 20 kHz), or alternatively, a phase-lock synchronization between shear wave-source and imaging device.